2021
DOI: 10.46586/tches.v2021.i3.235-274
|View full text |Cite
|
Sign up to set email alerts
|

Pay Attention to Raw Traces: A Deep Learning Architecture for End-to-End Profiling Attacks

Abstract: With the renaissance of deep learning, the side-channel community also notices the potential of this technology, which is highly related to the profiling attacks in the side-channel context. Many papers have recently investigated the abilities of deep learning in profiling traces. Some of them also aim at the countermeasures (e.g., masking) simultaneously. Nevertheless, so far, all of these papers work with an (implicit) assumption that the number of time samples in raw traces can be reduced before the profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Still, the authors considered only ''standard'' elements in the hyperparameter evolution and did not evolve custom ones. More recently, the SCA community turned its attention to deep learning-based SCA with no feature engineering [33], [34] and showed the benefits of using the extra information stemming from more features.…”
Section: Related Workmentioning
confidence: 99%
“…Still, the authors considered only ''standard'' elements in the hyperparameter evolution and did not evolve custom ones. More recently, the SCA community turned its attention to deep learning-based SCA with no feature engineering [33], [34] and showed the benefits of using the extra information stemming from more features.…”
Section: Related Workmentioning
confidence: 99%
“…To remove the implicit premise that both profiling and attacking traces are segmented prior to DL-PSCA, Lu et al [15] resort to proposing a network for end-to-end profiling attacks, that is, both the profiling and attacking phase used raw unsegmented traces. Consequently, the authors employed a sophisticated feature extractor comprising locally-connected layers, LSTM, and attention mechanism.…”
Section: A Related Workmentioning
confidence: 99%
“…Deep learning (DL) has been widely investigated as an alternative profiling SCA solution in the last few years. The results with real-world datasets have demonstrated that deep neural networks provide several practical advantages in comparison to GTA, such as skipping points-of-interest or feature selection from raw measurements [14,19], relaxing assumptions about underlying leakage distribution, and being less sensitive to trace desynchronization [7,25,29]. However, together with large training times, the main open challenge for DL-based SCA is hyperparameter tuning.…”
Section: Introductionmentioning
confidence: 99%